An Intertestamental Apocalypse: the Book of Four Ezra - Onișor, Remus (Napoca Roots, 2021)
Book 4 Ezra is a magnificent literary production of Judaic origin. Here we find a profound moral vision and a highly literary way of thinking. The book is a historical apocalypse, reflecting the crisis, that will lead to the destruction of the Temple by the army of the Roman general Titus. It is however an anthropological apocalypse because it speaks of man's destiny in a difficult world. In the book, we have a series of seven visions, which are divided into two parts: the first three visions consist of a threefold dialogue of Ezra with the angel Uriel, and the other four visions comprise the true apocalyptic part – the woman in mourning, the vulture with twelve wings and three heads, The Son of God and Ezra, the successor of Moses. Ezra's Apocalypse highlights the important role of fasting and prayer, which are true drivers of moral progress. The author of the book affirms the existence of two worlds, willed by God. At the end of this world, the Messiah will come and establish a new kingdom. The law is presented as a guide and as a guardian. Ezra convincingly asserts the existence and presence of divine mercy in this world. The idea of a mediator, resurrected and full of glory, has Christian connotations.